A mixed-methods observational study of strategies for success in implementation science: overcoming emergency departments hurdles - Deonni P. Stolldorf; Alan B. Storrow; Dandan Liu; Cathy A. Jenkins; Rachel A. Hilton; Karen F. Miller; Joy Kim; Deepika Boopathy; Satheesh Gunaga; Bory Kea; Joseph Miller; Sean P. Collins (BMC Health Services Research)
Abstract Background Heart failure is a major public health concern, affecting 6.7 million Americans. An estimated 16% of emergency department (ED) patients with acute heart failure (AHF) are discharged home. Our Get with the Guidelines in Emergency Department Patients with Heart Failure (GUIDED-HF) toolkit aims to improve AHF self-care and facilitate safer transitions in care for these patients. We describe implementation barriers and facilitators, and the selection and refinement of implementation strategies, to facilitate future GUIDED-HF implementation. Methods A mixed-methods cross-sectional observational study was conducted in four United States EDs in two diverse healthcare systems in the Pacific West and Midwest. Data were collected using a survey and interviews with ED providers, nurses, and leaders. The survey assessed the ED context using the context scale of the Organizational Readiness to Change Assessment (ORCA). The Consolidated Framework for Implementation Research informed interviews. Quantitative data were summarized using medians (interquartile ranges) or percentages (frequencies). Wilcoxon rank-sum tests and Kruskal–Wallis tests were used to assess differences in the healthcare system and profession. Qualitative data were analyzed and summarized using rapid qualitative analysis. Convergence of quantitative and qualitative data was used to inform specific refining of implementation strategies to the local context (e.g., who should serve as champions, how best practice alerts should be implemented). Results Participants were predominately white (76%) with median (IQR) age 37.0 (32.0, 41.0). ED leaders/administrators, providers, and nurses comprised 15%, 55%, and 29% of participants, respectively. Sites reported an ORCA context scale score of 3.7 [3.4, 4.0] (scale of 1 = strongly disagree to 5 = strongly agree). Comparison of scores by profession showed a significant difference in the context score among providers (3.9 [3.5, 4.0]), leaders (3.7 [3.5, 4.0]), and nurses (3.6 [3.0, 3.9]) (p = 0.048). Qualitative data indicated implementation barriers (e.g., resource limitations, patient health literacy), facilitators (e.g., GUIDED-HF is patient-centric; site and intervention congruent values, norms, and goals), and site-specific needs due to contextual factors (e.g., education needs, feedback mechanisms, champions). Conclusions Specific determinants of implementation exist in ED settings and require the refining of implementation strategies to overcome site-specific barriers and enhance facilitators. Trial registration n/a.